2020
DOI: 10.1104/pp.20.00426
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Carbon Export and Nonstructural Carbohydrates in Relation to Diurnal Water Dynamics in Mature Oak Trees

Abstract: Trees typically experience large diurnal depressions in water potential, which may impede carbon export from leaves during the day because the xylem is the source of water for the phloem. As water potential becomes more negative, higher phloem osmotic concentrations are needed to draw water in from the xylem. Generating this high concentration of sugar in the phloem is particularly an issue for the ;50% of trees that exhibit passive loading. These ideas motivate the hypothesis that carbon export in woody plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 58 publications
3
27
1
Order By: Relevance
“…This is in apparent contrast to previous observations that have shown that leaves more exposed to sun usually have higher levels of soluble sugars when compared to shade leaves (Weerasinghe et al, 2014;Dayer et al, 2021). One explanation for the difference may be because our samples were collected during the early mornings where leaf NSCs may be depleted due to their use as respiratory substrates at night; leaf NSC concentrations tend to peak at midday when biosynthesis from photosynthesis is high (Dickman et al, 2019;Gersony et al, 2020). The lack of clear variation of leaf starch concentrations with canopy position may also be related to the fact that starch is a reserve carbohydrate with a slower turnover rate relative to sugars (Dickman et al, 2019).…”
Section: Relationships Between Respiratory Rates and Leaf Traitscontrasting
confidence: 66%
“…This is in apparent contrast to previous observations that have shown that leaves more exposed to sun usually have higher levels of soluble sugars when compared to shade leaves (Weerasinghe et al, 2014;Dayer et al, 2021). One explanation for the difference may be because our samples were collected during the early mornings where leaf NSCs may be depleted due to their use as respiratory substrates at night; leaf NSC concentrations tend to peak at midday when biosynthesis from photosynthesis is high (Dickman et al, 2019;Gersony et al, 2020). The lack of clear variation of leaf starch concentrations with canopy position may also be related to the fact that starch is a reserve carbohydrate with a slower turnover rate relative to sugars (Dickman et al, 2019).…”
Section: Relationships Between Respiratory Rates and Leaf Traitscontrasting
confidence: 66%
“…Furthermore, because bulk leaf osmolality is c . 935 mM at midday (Gersony et al ., 2020), some cells would need to have a much lower osmolality to balance out the osmolality of the cells with high cytoplasmic sucrose concentrations that are involved in passive loading. Such cellular‐level discrepancies in osmolality have not been observed in plasmolysis studies (Russin & Evert, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…A neighboring leaf was analyzed for sucrose content using the enzymatic‐colorimetric assay method described by Gersony et al . (2020) to establish the baseline concentration in the extract (average of 34 mM). The extract was then spiked with 0–1250 mM of sucrose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…genotype and phenological and physiological stages). In particular, diurnal variation in nonstructural carbohydrates in leaves can significantly affect osmotic pressure and thus leaf turgor (Charrier, 2020;Gersony et al, 2020).…”
Section: Extrapolating Physiological Response To Drought Throughmentioning
confidence: 99%